Analysis of Student’s Needs in Speaking Skill as The Basis for Developing Learning Materials on 8 Grades of MTs. Fathimatul Amin Jakarta - Minkhatunnakhriyah Minkhatunnakhriyah; Albiansyah Albiansyah (Instructional Development Journal, 2020)
Abstract: The aim of this study was how student’s need in speaking skill to design learning materials and to know student’s need in speaking skill to design learning materials in Junior high school level. Therefore, the participants of this study were 8 grades of Junior high school on Fathimatul Amin Jakarta. The data were collected through the questionnaire and focused on their need analysis in speaking skill as the basis to develop learning materials. Result of this study shows that from two-part which target needs and student need. From target need the result show most of them likes to study English subject. However, in their speaking English were at a basic level because they assume it was a difficult skill. So, from the need analysis result in the lack in practising speaking skill were low of vocabularies, grammar, afraid on wrong pronunciation, therefore their need to enhance their speaking was the activities of learning English process trough discussion in pairs by daily need topic and add their vocabularies by looking for some words from reading text and get grammar explanation from the teacher before practising speaking skill. Abstrak: Tujuan dari penelitian ini adalah bagaimana kebutuhan siswa dalam keterampilan berbicara dalam mendesain materi pembelajaran dan untuk mengetahui kebutuhan siswa dalam keterampilan berbicara dalam merancang materi pembelajaran di tingkat SMP. Oleh karena itu, partisipan penelitian ini adalah siswa kelas 8 SMP di Fathimatul Amin Jakarta. Pengumpulan data dilakukan melalui kuesioner dan difokuskan pada analisis kebutuhan keterampilan berbicara sebagai dasar untuk mengembangkan materi pembelajaran. Hasil penelitian ini menunjukkan bahwa dari dua bagian yaitu kebutuhan sasaran dan kebutuhan siswa. Dari hasil kebutuhan target menunjukkan sebagian besar dari mereka suka belajar bahasa Inggris. Namun, dalam berbicara bahasa Inggris mereka berada pada tingkat dasar karena mereka menganggap itu adalah keterampilan yang sulit. Sehingga dari hasil analisis kebutuhan dalam praktek keterampilan berbicara kurang kosakata, tata bahasa, takut salah pengucapan, oleh karena itu kebutuhan mereka untuk meningkatkan kemampuan berbicara mereka adalah kegiatan pembelajaran bahasa Inggris melalui diskusi berpasangan dengan topik kebutuhan sehari-hari dan menambahkan kosa kata mereka dengan mencari beberapa kata dari teks bacaan dan mendapatkan penjelasan tata bahasa dari guru sebelum mempraktikkan keterampilan berbicara.